Separate and unequal - King, Desmond (Oxford University Press, 2007)
In this landmark book, Desmond King reveals and corrects a glaring gap at the epicenter of studies of racial inequality and political development in the United States: their blindness to the pivotal role of the state in making race. With historical precision and analytic rigor, he demonstrates how, for seven decades following the legal affirmation of the doctrine 'separate and equal' in 1896, the federal government both bolstered and expanded racial separation, in effect nationalizing the pattern of black subordination elaborated by Southern segregationists in the aftermath of abolition... African Americans in the civil service,African Americans 173 11488 eng 0198574002 w1w 9780198574002 612.821 P622 edited by P. Maquet, C. Smith and R. Stickgold xvi, 379 p. Sleep and brain plasticity ill. 25 cm Oxford,New York Oxford University Press 2003 Sleep w1w Dreams w1w Neuroplasticity Sleep has long been a topic of fascination for artists and scientists. Why do we sleep? What function does sleep serve? Why do we dream? What significance can we attach to our dreams? We spend so much of our lives sleeping, yet its precise function is unclear, in spite of our increasing understanding of the processes generating and maintaining sleep. We now know that sleep can be accompanied by periods of intense cerebral activity, yet only recently has experimental data started to provide us with soem insights into the type of processing taking place in the brain as we sleep. There is now strong evidence that sleep plays a crucial role in learning and in the consolidation of memories. Once the preserve of psychoanalysts, 'dreaming' is now a topic of increasing interest amongst scientists Sleep,Dreams,Neuroplasticity Carlyle Smith,Robert Stickgold,Pierre Maquet 174 11491 eng 9780195170450 w1w 0195170458 200.973 M334 Griffith, R. Marie a documentary history R. Marie Griffith xxiv, 637 p. American religions ill. 24 cm Griffith, R. Marie New York Oxford University Press 2008 United States Balancing canonical works with those by newly discovered voices, American Religions: A Documentary History includes seventy-five classic and contemporary selections from the colonial period through the present day. It offers readings by a uniquely wide range of religiously, socially, and ethnically diverse writers: theological conservatives and liberals, northerners and southerners, women and men, and African Americans and Mexican Americans alongside Anglo-Americans. The selections are long enough to stimulate serious discussion yet concise enough for students to digest easily. The volume is organized into six sections that cover different chronological periods, each of which contains writings on five themes: theological reflections, ritual and performance, spiritual autobiography, interreligious conflict and negotiation, and more expansive conceptualizations of religion. Enhanced by brief biographies of the authors, a general introduction, and section introductions, the text also includes two sample syllabi--one oriented toward a historical approach and the other toward a thematic approach. Ideal for introductory courses in religion in America 175 11511 eng 0195334590 305.420973 W758 Winifred Breines an uneasy history of white and Black women in the feminist movement Winifred Breines viii, 269 p. The ill. 24 cm Winifred Breines Oxford,New York Oxford University Press 2007 Feminism w1w African American feminists w1w Women radicals Drawing on flyers, letters, newspapers, journals, institutional records, and oral histories, Breines dissects how white and black women's participation in the movements of the 1960s led to the development of separate feminisms. Herself a participant in these events, Breines attempts to reconcile the explicit professions of anti-racism by white feminists with the accusations of mistreatment, ignorance, and neglect by African American feminists. Many radical white women, unable to see beyond their own experiences and idealism, often behaved in unconsciously or abstractly racist ways, despite their passionately anti-racist stance and hard work to develop an interracial movement. As Breines argues, however, white feminists' racism is not the only reason for the absence of an interracial feminist movement Feminism,African American feminists,Women radicals 176 11512 eng 0198566328 w1w 9780198566328 616.944 R888 a practical guide edited by Roy A.J. Spence, Roderick J. Hay, Patrick G. Johnston x, 271 p. Infection in the cancer patient ill. (some col.) 24 cm Oxford,New York Oxford University Press 2006 Cancer w1w Cancer w1w Neoplasms w1w Immunotherapy w1w Infection w1w Infection w1w Sepsis Includes bibliographical references and index Infection in the cancer patient is extremely common, either precipitated by the cancer itself or occuring as a consequence of cancer therapies. Virtually all cancer patients develop an infection during their illness, many of which are life-threatening and require urgent treatment. There are also the wider health implications of antibiotic resistance and hospital acquired infections. This book provides a practical guide to all the infections a practising clinician and members of the multi-disciplinary team will meet in their care of a cancer patient. An overview of the problem of infection in the cancer patient is provided, covering the immunology of cancer and the infection sequelae. This is then developed by site specific chapters, each describing the organisms responsible for the infection, its presentation, appropriate investigations, and finally management advice. Unique groups explored include viral infections such as HIV and infections in paediatrics. Infections in end of life care are specifically addressed.Written by an international team of contributors recognised in their field, this book is the first to concentrate on what is a major issue for anyone involved in the care of the oncology patient Cancer,Cancer,Neoplasms,Immunotherapy,Infection,Infection,Sepsis Hay, R. J.,Spence, Roy A. J.,Johnston, Patrick G. 177 11539 eng 0198631537 w1w 9780198631538 427.96303 D212 managing editor, Penny Silva ; editors, Wendy Dore ... [et al.] xxix, 825 p. A 29 cm Oxford,New York Oxford University Press 1996 English language w1w English language Includes bibliographical references (p. [811]-825) This Dictionary documents the development of English in South Africa from the late sixteenth century to the present day. It covers words originating in all the country's ethnic groups and communities. 47,000 quotations illustrate 8,000 entries from literature, conversations, and radio and television broadcasts English language,English language Silva, Penny Rhodes University Dictionary Unit for South African English 178 267 Vie 371.425 T455 Tổng cục dạy nghề 51 tr. Nghề trang điểm thẫm mỹ 27 cm Hà Nội Lao động Thương binh và Xã hội 2000 179 7439 Vie Viện Khoa Học Xã Hội Việt Nam 96 p Tạp Chí Nghiên Cứu Gia Đình & Giới Số 6, Đinh Công Tráng - Hà Nội 2010 180 7443 eng 0324323441 w1w 9780324323443 339 B347 Baumol, William J. William J. Baumol, Alan S. Blinder 401 p. Macroeconomics Principles and Policy ill. 28 cm Baumol, William J.,Blinder, Alan S. Mason, Ohio Thomson/South Western 2006 Macroeconomics w1w Microeconomics This macroeconomics text is well known for using the Keynesian model in the teaching of economics; yet in recent editions, the authors have expanded coverage of the growth model considerably to achieve more balanced coverage. The text uses the aggregate supply/ aggregate demand model as a fundamental tool for learning macroeconomics. It achieves the right level of rigor and detail, presenting complicated concepts in a relatively straightforward manner and using timely economic data. Using puzzles, issues, and well-developed examples, the authors provide a good balance of theory to application. Homework Xpress and Aplia are available with the Anniversary Tenth Edition and two new sets of end of chapter questions have been added as well to help students prepare for exams: Test Yourself and Discussion Questions Macroeconomics,Microeconomics Blinder, Alan S. 181 7809 eng 0534274080 w1w 9780534274085 515 S851 Stewart, James James Stewart 1204, 136 p. Calculus ill.